A Possible Tram–Train System Covering Bratislava Old Bridge—Petrzalka Railway Station - Tibor Schlosser; Gabriel Bálint; Matúš Korfant; Peter Schlosser (Applied Sciences, 2025)
Bratislava is currently experiencing massive development, and its developers are very active. As the city develops, the improvement of its public transport becomes increasingly crucial. Public transport (PT) must be ecological, economical, and accessible to all social groups of the population. Bratislava currently has the opportunity to change the modal split in favor of PT and thus end the decline that began in the early 1990s. Rail transport is an ecological type of PT incorporated into smart cities, contributing to city land use. The current PT rail track in Bratislava comprises tram and train infrastructure. Trains ensure the transportation of people from the municipalities surrounding Bratislava, while trams ensure the transportation of people within the city. Tram and train PT must be merged, as their integration could improve traveling times. Bratislava is suitable for the creation of a dual rail transport system covering the urbanized area. The goal of this article is to present a technical solution for a double-gauge system for operation, considering traffic engineering and planning to aid decision making. Considerable professional and expert work was undertaken, in contrast to the political administration’s “decision making”. Cases from Central Europe are presented.